Challenges to the Profitability of Fintech Companies - Dimitrova, Ralitsa (Economy and Business Yearbook, 2022)
This paper examines the specifics of the business model and financing method of fintech companies. Despite the boom in fintech startups in the financial services sector, most of them face significant difficulties in reaching a breakeven point, profitability and long-term survival. The current trends in investments in this sector are presented and, on this basis, four main challenges for fintech companies on their way to achieving profitability are identified - removing the gaps in the business model, increasing the financial efficiency at the product/service level, change in the competitive environment and meeting regulatory challenges.